Evaluasi Program Musyawarah Guru Mata Pelajaran Fisika SMA di Kabupaten Pangkep - Kaharuddin Arafah; Muamar Qadar; Triyanto Pristiwaluyo (Department of Physics Education, Universitas Mataram, 2020)
The teacher as an important figure in learning to encourage students to achieve high learning outcomes. In carrying out their activities, teachers who are members of the Physics Consultative Association (MGMP) of Physics in Pangkep Regency need to be evaluated. This research aims to plan the preparation, implementation and results of the Physics MGMP program in Pangkep Regency. To achieve these objectives, evaluative research has been conducted using the Countenance StakeÃ¢â¬â¢s model. The subject of this research was the High School Physics Teacher Study Program (MGMP) in Pangkep Regency. Data collection uses interviews, observation, and documentation. Data were analyzed using the qualitative model of Miles and Huberman. Data analysis consists of three activities: data condensation, data display and conclusions. The results of data analysis that prove the evaluation of preparation is in accordance with the guidelines used. Implementation evaluation is in accordance with the guidelines used, but it needs to be on several aspects. Program evaluation of MGMP results depends on either category. Based on the evaluation findings of this program, it can be recommended that the MGMP program in Pangkep Regency can be continued with several improvements. So that the preparation is more optimal. While on the implementation schedule, active participants need to be optimized, and need an agenda related to the needs of teachers in the field.